Exploring the dimensions of local food tourism in Cirebon - Sri Widya Wijanarti; Ambara Purusottama (Universitas Merdeka Malang, 2022)
The sustainability of a tourist destination can be achieved by correctly planning, exploiting, and growing the area's tourism potential. Local gastronomy is one of the potentials that can be cultivated. Local cuisine has evolved into a driving force in enticing tourists to a destination. The goal of this research is to better understand the consumption habits of local food tourists. A food tourism framework is defined in this study, which includes culinary attribute, culinary experience, and culinary atmosphere. A total of 337 people who participated in a cuisine tour in Cirebon were surveyed to test the framework that has been built. Data was processed using descriptive statistical methods, followed by cross analysis using the Independent Sample T-Test on measurement results that had been adjusted to the respondents' attributes. The data demonstrate a strong response to culinary attribute, culinary experience, and culinary atmosphere. This research provides practitioners and stakeholders with a new perspective on what should be a concern in the development of culinary tourism in Cirebon. This study adds to the food tourism literature by elaborating on the notion of local food tourism, which is articulated effectively in this study.